Impact of obesity in the elder woman’s health - Lissón Abanto, Rosa (2018)
The world’s population has aged and is becoming more feminine. The adult women suffer the negative impact of ageing and ovarian failure, with low levels of estrogen in the menopause. In up to 33% of them the body weight increases in range of overweight or obesity, with redistribution of fat in the visceral region and reduction of lean mass. This predisposes it to all comorbidities associated with obesity as well as metabolic and cardiovascular diseases and mortality at younger age than their peers with normal weight. Life expectancy has increased. Therefore it would be ideal to add to these quality years, living free of chronic and disabling illnesses and as much as possible to make them self-sufficient and independent. We should intervene to find intentional weight loss in those who have it increased, reducing mortality and morbidity that increase with obesity.